Visfatin Amplifies Cardiac Inflammation and Aggravates Cardiac Injury via the NF-κB p65 Signaling Pathway in LPS-Treated Mice. (10th October 2022) - Hu, Yewen; Wu, Nan; Du, Weiping; Wang, Shuangshuang; Wang, Jian; Zhang, Chaoxia; Chen, Xiaomin; Shen, Caijie
Abstract : Background . Visfatin is an adipocytokine that has been demonstrated to be involved in cardiovascular diseases. This study aims at determining the role of visfatin in sepsis-induced cardiac injury and identify its possible mechanisms. Methods. Dynamic changes in visfatin expression in mice with lipopolysaccharide- (LPS-) induced septicemia were measured. Additionally, mice were pretreated with visfatin and further administered LPS to observe the effects of visfatin on cardiac injury. Finally, septic mice were also pretreated with JSH-23 to investigate whether visfatin regulates cardiac injury via the NF- κ B p65 pathway. Results. Visfatin expression levels in both the heart and serum were increased in LPS-treated mice and peaked at 6 hours, and visfatin was derived from cardiac macrophages. In septic mice, pretreatment with visfatin reduced the survival rate, worsened cardiac dysfunction, and increased the expression of cardiac injury markers, including creatine kinase myocardial bound (CK-MB) and lactate dehydrogenase (LDH). Treatment with visfatin also increased the infiltration of CD3+ cells and F4/80+ cells, amplified the cardiac inflammatory response, and elevated myocardial cell apoptosis. Treatment with JSH-23 reversed the effects of visfatin in septic mice. Conclusions. This study showed that visfatin amplifies the cardiac inflammatory response and aggravates cardiac injury through the p65 signaling pathway. Visfatin may be a clinical target for preventing cardiac injury in sepsis.